The association of single nucleotide polymorphism (SNP) rs2922126 within ghrelin and growth hormone secretagogue receptor 1a (GHSR1a) gene with insulin resistance in obese female adolescents in Yogyakarta Special Region - Madarina Julia, Cut Gina Inggriyani Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Previous study reported that among 79 obese female adolescents in Yogyakarta Special Region, 44 (55.7%) of them have insulin resistance. However, no significant differences on dietary habits and physical activity between the obese female who have insulin resistance and thosewho are insulin sensitive were observed. Therefore, it was thought that genetic factors are involved in the occurrence of insulin resistance. Ghrelin and growth hormone secretagogue receptor (GHSR) genes have been associated with the insulin signaling pathway with implicationsin insulin resistance. The study aimed to analyze the association between SNP (single nucleotid polymorphism) rs2922126 in GHSR1a gene with insulin resistance in obese female adolescents in Yogyakarta Special Region. Seventy eight obese female adolescents who were selected in theprevious study were involved in this study. Secondary data including name of subjects, age, body height, body weight, BMI (body mass index), fasting glucose level, fasting insulin level, waist circumference and HOMA-IR index were obtained from previous study. Polymerase Chai Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP) methods were used to the genotype analysis of SNP rs2922126. Chi-square test was used to calculate odds ratio on genotype and allele of SNP rs2922126 GHSR1a gene in insulin resistance and insulin sensitive groups. The results showed that A/A genotype individuals in SNP rs2922126 had higher risk to develop insulin resistance, compared to A/T and T/T genotypes individuals (OR: 2.03; 95%CI: 0.54-7.57). However, it was not significantly different (p>0.05). Individuals with A/A genotype and A allele carriers at SNP rs2922126 tended to have a higher value of BMI, fasting glucose level, fasting insulin level, HOMA-IR, and waist circumference compared to other carriers, althoughit was not significant (p>0.05). It can be concluded that SNP rs2922126 in GHSR1a gene is not associated with insulin resistance in obese female adolescents in Yogyakarta Special Region.Keywords: GHSR1a gene - SNP rs2922126 - insulin resistance - female - obese